2016
DOI: 10.1016/j.jvs.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve injury is associated with dual antiplatelet therapy use and cervical hematoma after carotid endarterectomy

Abstract: CNI is predominantly a transient complication, but is associated significantly with dual antiplatelet therapy use and the occurrence of a postoperative cervical hematoma. Scrupulous attention to hemostasis might reduce the incidence of CNI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Following abstract and full text screening, eight studies were included for analysis. 9,11,15,25e29 In addition, the authors of nine articles responded to the request for additional information, 6,30e37 and these were added if they met the inclusion criteria, 31,32,36 resulting in a total of 11 articles (Table 1). Across these studies, there were 47 411 patients, with 33 066 (69.7%) in the aspirin arm and 14 345 (30.3%) patients in the DAPT arm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following abstract and full text screening, eight studies were included for analysis. 9,11,15,25e29 In addition, the authors of nine articles responded to the request for additional information, 6,30e37 and these were added if they met the inclusion criteria, 31,32,36 resulting in a total of 11 articles (Table 1). Across these studies, there were 47 411 patients, with 33 066 (69.7%) in the aspirin arm and 14 345 (30.3%) patients in the DAPT arm.…”
Section: Resultsmentioning
confidence: 99%
“…Across these studies, there were 47 411 patients, with 33 066 (69.7%) in the aspirin arm and 14 345 (30.3%) patients in the DAPT arm. Studies reported in hospital or peri-operative outcomes 9,25,28,31 or 30 day outcomes, 15,26,32 and these were pooled for statistical analysis. The overall level of evidence was low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative cranial nerve injury was reported in 2.2% to 5.6% of cases. [26][27][28] A recent review of cranial nerve injury after CEA reported rates of vagus nerve injury, hypoglossal…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent controversy about the bleeding risk associated with perioperative clopidogrel use in vascular surgery (particularly for carotid endarterectomy [CEA]), 1218 it has become increasingly clear that clopidogrel is associated with bleeding complications. Compared with LEB, bleeding after CEA is less likely to be associated with transfusion and more likely to lead to reoperation because of the severe consequences of ongoing blood loss.…”
Section: Discussionmentioning
confidence: 99%